DATA FLOW DIAGRAM (DFD) PADA APOTEK CANDRA KOTA JAMBI - Yunan Surono (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Apotek Candra is a trading business engaged in the sale of drugs, which in the process of doing business is still using manual systems. This can lead to many mistakes in recording, so that the resulting data is not accurate. To view information from the data processing requires a process that takes a long time. Because it takes a design and manufacturing information system that can manage the data so as to generate information in the form of a well-organized report. Designing a new system design that uses Data Flow Diagrams (DFD).Keywords: Data Flow Diagrams (DFD)